Analysis on the effectiveness of co-solute on the network integrity of high methoxy pectin - Almrhag, O.; George, P.; Bannikova, A.; Katopo, L.; Chaudhary, Deeptangshu; Kasapis, S. (Elsevier, 2012)
Co-solute requirements for high methoxy pectin gelation were observed by the addition of glucose syrupand polydextrose at concentrations varying from 50% to 78% (w/w). Pectin content was fixed at 2% (w/w) in formulations. Studies from small deformation dynamic oscillation in shear, modulated differentialscanning calorimetry and environmental scanning electron microscopy are reported. Structural properties of pectin preparations were recorded in relation to the molecular weight and concentration of added co-solute in an acidic environment (pH ~3.0). High levels of co-solute induce formation of weak pectin gels at elevated temperatures (even at 95 °C), which upon subsequent cooling exhibit increasing strength and convert to a clear glass at subzero temperatures. Fourier Transform Infrared Spectroscopy and wide angle X-ray diffraction were practised to examine the nature of interactions between polymer and co-solute and the extent of amorphicity of preparations. Glucose syrup is an efficient plasticiser leading to a reduction in the glass transition temperature (Tg) of the pectin network, whereas polydextrose assists in the formation of stronger pectin gels in the rubbery state.